Climate change impacts on the atmospheric circulation, ocean, and fisheries in the southwest South Atlantic Ocean: a review - Franco, Bárbara C.; Defeo, Omar; Piola, Alberto R.; Barreiro, Marcelo; Yang, Hu; Ortega, Leonardo; Gianelli, Ignacio; Castello, Jorge P.; Vera, Carolina; Buratti, Claudio; Pájaro, Marcelo; Pezzi, Luciano P.; et al. (Climatic change, 2020)
We present an interdisciplinary review of the observed and projected variations in atmospheric and oceanic circulation within the southwestern South Atlantic focused on basin-scale processes driven by climate change, and their potential impact on the regional fisheries. The observed patterns of atmospheric circulation anomalies are consistent with anthropogenic climate change. There is strong scientific evidence suggesting that the Brazil Current is intensifying and shifting southwards during the past decades in response to changes in near-surface wind patterns, leading to intense ocean warming along the path of the Brazil Current, the South Brazil Bight, and in the Río de la Plata. These changes are presumably responsible for the poleward shift of commercially important pelagic species in the region and the long-term shift from cold-water to warm-water species in industrial fisheries of Uruguay. Scientific and traditional knowledge shows that climate change is also affecting small-scale fisheries. Long-term records suggest that mass mortalities decimated harvested clam populations along coastal ecosystems of the region, leading to prolonged shellfishery closures. More frequent and intense harmful algal blooms together with unfavorable environmental conditions driven by climate change stressors affect coastal shellfisheries, impact economic revenues, and damage the livelihood of local communities. We identify future modelling needs to reduce uncertainty in the expected effects of climate change on marine fisheries. However, the paucity of fisheries data prevents a more effective assessment of the impact of climate change on fisheries and hampers the ability of governments and communities to adapt to these changes.